1999
DOI: 10.1109/77.783353
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for high field HTS magnets

Abstract: Six partners from five European countries are cooperating within a R&D BRITE EURAM project named SHIFT" (Superconducting High Tc Coils for High Field Technologies). The objective of this 3-year project is to develop basic technologies for manufacturing magnets producing high fields operating in the temperature range 20-30 K: HTS wires, coils based on bulk parts, coil structures and cooling system. The potential applications are pulsed magnets for power quality SMES and DC magnets for MRI, instrumentation and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus a temperature sensor may not detect a developing quench in time. The use of some kind of heat drains for improving the thermal conductivity in the magnet [16,17] would help the situation much. The quench detection based on monitoring the voltage over a coil section is not straightforward either.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a temperature sensor may not detect a developing quench in time. The use of some kind of heat drains for improving the thermal conductivity in the magnet [16,17] would help the situation much. The quench detection based on monitoring the voltage over a coil section is not straightforward either.…”
Section: Discussionmentioning
confidence: 99%
“…However, the obvious anisotropy electromagnetic character makes the design of the HTS magnet is different with the LTS magnet design. It is well known that in HTS materials are more sensitive to magnetic fields perpendicular to the wide face of the HTS tape than to fields parallel to the wide face of the HTS tape [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many studies and developments of HTS SMES have been carried out. In [28], it was reported that six partners from five European countries cooperated within an R&D BRITE EURAM project named SHIFT to develop basic technologies for manufacturing magnets producing high fields operating in the temperature range 20-30 K. One of the potential applications is pulsed magnets for SMES, which is used to smooth the voltage sags and to mitigate flicker. Within the Italian project for the development of 1 MJ/1 MW SMES, the SMES system had 1100 A resistive/HTS current leads conduction-cooled by a closed cycle refrigerator in the temperature range 60-70 K [29].…”
Section: Introductionmentioning
confidence: 99%